Assessment of Novel Muscarinic Acetylcholine Receptors in Rat Cerebral Cortex by a Tissue Segment Binding Method - Kung-Shing Lee; Atsushi Nishimune; Hatsumi Yoshiki; Abu Syed Md Anisuzzaman; Fumiko Suzuki; Mao-Hsien Wang; Juei-Tang Cheng; Ikunobu Muramatsu (Elsevier, 2010)
Muscarinic acetylcholine receptors (mAChRs) of rat cerebral cortex were evaluated using a tissue segment radioligand binding assay. [3H]-Quinuclidinyl benzilate (QNB, a hydrophobic ligand) specifically bound to mAChRs in the cortex segments. The total mAChRs level was approximately 2,000 fmol/mg protein, which was estimated after incubation for 120 min at 37°C or for 8 h at 4°C. These mAChRs were a mixture of high- and low-affinity sites for N-methylscopolamine (NMS) in a 70:30 ratio. In contrast, only a single high-affinity site for NMS was detected following incubation for 30 min at 37°C, whose abundance was about 70% of that of the total mAChRs. Atropine showed a single affinity for mAChRs under all conditions. These indicate that mAChRs are constitutively expressed not only on plasma membrane sites but also at intracellular sites in rat cerebral cortex and that the receptors at both sites have different affinities for NMS. Acetylcholine completely inhibited [3H]-QNB binding to both mAChRs without any change in the subcellular distribution, suggesting the possibility that acetylcholine can access, and bind to, both mAChRs in intact tissue. Two different affinity states for acetylcholine were detected only in plasma membrane mAChRs at 37°C. The present study demonstrates a unique subcellular distribution, and distinct pharmacological profiles, of mAChRs in rat cerebral cortex. Keywords:: muscarinic acetylcholine receptor, intracellular receptor, quinuclidinyl benzilate, rat cerebral cortex, tissue segment binding assay